A study of 'self-repair' operations in conversation by Chinese English learners. (April 2015) - Quan, Lihong; Weisser, Martin
Abstract: Based on data extracted from the Chinese component of the LINDSEI corpus and its native speaker counterpart LOCNEC, this paper examines the similarities and differences between Chinese English learners and English native speakers in the use of recycling and replacement, two very common forms of 'self-repair'. The data were analysed with a focus on two aspects: the syntactic class of words both learners and native speakers tend to initiate recycling and replacement in, and which types of syntactic/lexical elements are most frequently repeated. The results of the study indicate that Chinese English learners employ more recycling and replacement than native speakers. The most striking finding is that Chinese English learners utilise more verbs to initiate recycling and as replaced items than native speakers, which has significant implications for both vocabulary and grammar teaching. Another important finding is that both Chinese English learners and native speakers use more word-level recycling than group-level recycling, which partly contradicts those in earlier studies. The findings are discussed with reference to morpho-syntactic patterns of English, combined with theories of attention and automaticity in L2.